Mózgi w naczyniu - Albiński, Tomasz (Filozofia Publiczna i Edukacja Demokratyczna, 2012)
Although there is a disagreement about how Putnam’s argument should be understood, it is possible to point to several elements of this argument which are common for many different reconstructions. In this paper I have tried to show that not all of them are unquestionable. And I want to propose a new way in which self-refutation of statement „I am a brain in a vat” may be understood. A form of this reconstruction is neutral for controversy about metaphysical realism or skepticism – it differs from the argument suggested by Putnam’s text. But I think that a story about envatted brains is simply a story about a language.